2016
DOI: 10.1093/scan/nsw075
|View full text |Cite
|
Sign up to set email alerts
|

‘Just can’t hide it’: a behavioral and lesion study on emotional response modulation after right prefrontal damage

Abstract: As a group, individuals with rPFC damage presented a significantly reduced range of response modulation compared with controls. In addition, performance in the suppression task was associated with measures of cognitive inhibition and suppression usage. Interestingly, these effects were driven primarily by a subgroup of individuals with rPFC damage, all of whom also had damage to the right posterior insula, and who presented a marked impairment in suppressing facial emotional expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…There is considerable evidence showing that emotion regulation in general is related to executive functioning (EF), such that higher EF is associated with more successful expressive suppression (Gyurak et al, 2012;Schmeichel et al, 2008) and reappraisal (Schmeichel & Tang, 2015). Consistent with these associations, the networks that subserve these emotion regulation strategies overlap with EF networks, involving multiple regions of the prefrontal cortex, evidenced by both imaging and lesion studies (Abler et al, 2008;Giuliani et al, 2011;Hermann et al, 2014;Ohira et al, 2006;Salas et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…There is considerable evidence showing that emotion regulation in general is related to executive functioning (EF), such that higher EF is associated with more successful expressive suppression (Gyurak et al, 2012;Schmeichel et al, 2008) and reappraisal (Schmeichel & Tang, 2015). Consistent with these associations, the networks that subserve these emotion regulation strategies overlap with EF networks, involving multiple regions of the prefrontal cortex, evidenced by both imaging and lesion studies (Abler et al, 2008;Giuliani et al, 2011;Hermann et al, 2014;Ohira et al, 2006;Salas et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, a recent study on patients with brain tumours (Campanella et al ., ) did not find effects related to hemispheric lateralization; moreover, this study revealed that temporal and insular lesions, but not frontal ones, affected emotion recognition; frontal lesions were instead associated with alexithymia symptoms, measured by a clinical questionnaire. Concerning emotion regulation, recent studies report similar impairments in emotional reappraisal in right and left brain‐damaged patients compared to healthy controls (Salas, Gross, & Turnbull, ), but also difficulties in positive emotion suppression in patients with right frontal damage and, particularly, right insula lesions (Salas et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, it has been shown that expressing anger is related to relatively greater left, whereas controlling anger is related to relatively greater right, frontal ac-tivity (Hewig et al, 2004). The role of the right PFC in affect regulation is further supported by lesion (e.g., Salas et al, 2016) and neuroimaging (for review, see Ochsner et al, 2012) studies.…”
Section: Introductionmentioning
confidence: 98%